2019
DOI: 10.1088/1748-9326/ab17fb
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on Canadian yields of spring wheat, canola and maize for global warming levels of 1.5 °C, 2.0 °C, 2.5 °C and 3.0 °C

Abstract: Science-based assessments of climate change impacts on cropping systems under different levels of global warming are essential for informing stakeholders which global climate targets and potential adaptation strategies may be effective. A comprehensive evaluation of climate change impacts on Canada's crop production under different levels of global warming is currently lacking. The DayCent, DNDC and DSSAT models were employed to estimate changes in crop yield and production for three prominent crops including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 59 publications
5
43
0
Order By: Relevance
“…Studies have reported that climate change and variability manifested in changing rainfall patterns and temperature, determines water availability for growth and production of crops with direct effects on crop yields 31 – 34 . An increase in global temperature by 2 °C, for example, can potentially lead to a 17% reduction in crop yields 35 , 36 , most especially those very sensitive crops, such as maize and rice, and this may result in reduction of yields in SSA 37 , 38 . In the case of maize for example, though the seed germinates at a temperature range of 18–21 °C, it can be grown in both rainy and dry seasons provided adequate water is available during germination and the first month of growth.…”
Section: Environmental and Pest Challenges Overlapped The Movement Rementioning
confidence: 99%
“…Studies have reported that climate change and variability manifested in changing rainfall patterns and temperature, determines water availability for growth and production of crops with direct effects on crop yields 31 – 34 . An increase in global temperature by 2 °C, for example, can potentially lead to a 17% reduction in crop yields 35 , 36 , most especially those very sensitive crops, such as maize and rice, and this may result in reduction of yields in SSA 37 , 38 . In the case of maize for example, though the seed germinates at a temperature range of 18–21 °C, it can be grown in both rainy and dry seasons provided adequate water is available during germination and the first month of growth.…”
Section: Environmental and Pest Challenges Overlapped The Movement Rementioning
confidence: 99%
“…Process-based models are valuable tools in evaluating management practices and climate change impacts on crop production, soil water balance and carbon (C) & N dynamics in diverse agroecosystems 20,21 . The DSSAT model is a widely used tool for testing cropping technologies, assessing management practices, and exploring climate change mitigation stategies 14,[21][22][23][24] . The DSSAT model has been successfully used to optimize field management practices to achieve high crop yield, improve understandings of crop physiology, soil management and weather effects on crop growth and environmental quality 25,26 , and explore the responses of crop production to climate change and develop effective adaptation strategies 10,12,14,27 .…”
mentioning
confidence: 99%
“…Sorghum and millet: Sorghum and millet are two possible crops to move into the drier areas of the prairies in 2050. These crops represent a possible feed grain for the driest areas, but sensitivity to frost will limit area even with increased growing season [25].…”
Section: Biophysical Impacts On Crop Productionmentioning
confidence: 99%